Exploring the effects of quercetin-added pancreatic diet on metabolic homeostasis in dogs via metabolomics - Xiao-Wan Liu; Yao-hui Zhang; Li Xu; Jia-Bao Xing; Zhou-xiang Wang; Man-li Hu; Yun Chen; Zhi-li Qi; Yi Ding; Xin Zhang; Ming-Xing Ding; Xiao-Jing Zhang; et al. (PLoS ONE, 2025)
Objective To investigate the role of quercetin-added pancreatic prescription food in regulating metabolic homeostasis in dogs. Methods The experimental dogs were divided into a control diet group and a prescription diet group. The control group was fed regular food, while the prescription group was fed pancreatic prescription food (3.9 g of quercetin was added in per 1 kg of food) for 8 weeks. Canine physical examination, complete blood count, and serum biochemical tests were conducted at 0 w, 4 w, and 8 w. Non-targeted metabolomics tests were performed using plasma samples at 0 w and 8 w. Results Dogs that received a quercetin-added pancreatic diet supplemented with quercetin showed no changes in the body weight, fasting blood glucose, body condition score, the indexes of whole blood program of red blood cells, white blood cells and platelets, and most blood biochemical indexes, but increased lipase levels in plasma at 8 w. Quercetin significant improved in metabolic homeostasis, especially in fatty acid, amino acid, and bile acid metabolism. Untargeted metabolomics analysis revealed that quercetin activates ABC transport and arginine/proline pathways, suggesting potential benefits for pancreatitis in large animals, while maintaining comparable safety parameters. Conclusions Quercetin-added prescription food enhances fatty acid and amino acid metabolism, demonstrating its potential to promote pancreatic function and sustain metabolic homeostasis.